Human scale development of Venezuelan immigrants in San José de Cúcuta (2019)
The present study determines the differences between living conditions of Venezuelan immigrants in the border city of Cúcuta, Colombia, and their comprehension and vision of development from the approach of the human scale development. With focal interviews, a qualitative methodology was applied, which allowed the construction of an axiological and existential needs matrix with the Atlas Ti software, semantic networks of their current condition and development vision were also developed. The results suggest that: i) poverty exists in each of the needs studied; ii) the idea of development is determined to a greater extent, by economic stability; iii) there is no human scale development in the host society, which cuts off the possibility of improving quality of life.